Mainstreaming human and large carnivore coexistence through institutional collaboration. Issue 6 (21st June 2019) - Hartel, Tibor; Scheele, Ben C.; Vanak, Abi Tamim; Rozylowicz, Laurențiu; Linnell, John D. C.; Ritchie, Euan G.
Abstract: Achieving coexistence between large carnivores and humans in human‐dominated landscapes (HDLs) is a key challenge for societies globally. This challenge cannot be adequately met with the current sectoral approaches to HDL governance and an academic community largely dominated by disciplinary sectors. Academia (universities and other research institutions and organizations) should take a more active role in embracing societal challenges around conservation of large carnivores in HDLs by facilitating cross‐sectoral cooperation to mainstream coexistence of humans and large carnivores. Drawing on lessons from populated regions of Europe, Asia, and South America with substantial densities of large carnivores, we suggest academia should better embrace the principles and methods of sustainability sciences and create institutional spaces for the implementation of transdisciplinary curricula and projects; reflect on research approaches (i.e., disciplinary, interdisciplinary, or transdisciplinary) they apply and how their outcomes could aid leveraging institutional transformations for mainstreaming; and engage with various institutions and stakeholder groups to create novel institutional structures that can respond to multiple challenges of HDL management and human–large carnivore coexistence. Success in mainstreaming this coexistence in HDL will rest on the ability to think and act cooperatively. Such a conservation achievement, if realized, stands to have far‐reaching benefits for people and biodiversity. Abstract : Article impact statement : Mainstreaming coexistence of humans and large carnivores in human‐dominated landscapes requires cross‐sectoral, institutional collaboration. Abstract : Incorporación de la Coexistencia entre Humanos y Carnívoros Mayores por Medio de la Colaboración Institucional Resumen: Un reto importante para las sociedades mundiales es lograr la coexistencia entre los carnívoros mayores y los humanos en los paisajes dominados por el hombre (HDL, en inglés). Este reto no puede enfrentarse adecuadamente con las actuales estrategias sectoriales que se usan en la gobernanza de los HDL y con una comunidad académica dominada principalmente por sectores disciplinarios. La academia (las universidades y demás instituciones y organizaciones de investigación) debería realizar un papel más activo en la aceptación de los retos sociales que rodean a la conservación de los carnívoros mayores en los HDL al facilitar la cooperación intersectorial para incorporar la coexistencia entre humanos y dichos carnívoros. A partir de las lecciones aprendidas en las regiones pobladas por densidades abundantes de carnívoros mayores en América del Sur, Asia y Europa, sugerimos que la academia debería aceptar de mejor manera los principios y métodos de las ciencia de la sustentabilidad y crear espacios institucionales para la implementación de currículos y proyectos; reflexionar sobre las estrategias de investigación (es decir, disciplinaria, interdisciplinaria o transdisciplinaria) que aplican y cómo sus resultados podrían ayudar en fomentar las transformaciones institucionales para la incorporación; y participar junto a varias instituciones y grupos de accionistas para crear estructuras institucionales novedosas que puedan responder a los múltiples retos del manejo de los HDL y de la coexistencia entre humanos y carnívoros mayores. El éxito en la incorporación de esta coexistencia en los HDL dependerá de la habilidad para pensar y actuar cooperativamente. Tal logro de conservación, si se alcanza, promete tener beneficios de largo alcance para las personas y para la biodiversidad. 摘要: 在人类主导景观中实现人与大型食肉动物的共存, 是全世界面临的一个重要挑战。然而, 目前对人类主导景观的部门管理方法和主要由学科领域主导的学术团体尚不足以应对这一挑战。学术界 (大学及研究组织机构) 应通过促进跨部门合作, 在应对人类主导景观中大型食肉动物保护的社会挑战中发挥更积极的作用, 以实现人类与大型食肉动物共存的主流化。借鉴欧洲、亚洲和南美洲人口与大型食肉动物密集地区的经验, 我们建议学术界应进一步采取可持续发展的原则和方法, 创造制度空间以开展超学科课程和项目;思考所应用的研究方法 (单一学科、交叉学科和超学科) 及其研究成果如何帮助推动有利于主流化的机构改革;另外, 还应与各种机构和利益相关群体合作, 创造新的制度结构, 以响应人类主导景观管理和人与大型食肉动物共存的挑战。在人类主导景观中实现共存的成功与否将取决于思考和行动协作的能力。如果能够实现这样的保护成就, 将对人类和生物多样性产生深远的好处。【翻译: 胡怡思; 审校: 聂永刚】